The open road 2023 : 50 best road trips in the USA - Dunham, Jessica (Moon travel handbooks., 2023)
"Picture yourself behind the wheel, elbow, hooked over the open window, favorite song blaring, the endless horizon unfurling ahead of you. Get ready for an unforgettable journey"--